Turning Risk Reports into Action: A Critical Review of Behavioral Barriers to Effective Enterprise Risk Management - Tri Gunarsih; Muh Arief Effendi; Fran Sayekti (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2026)
This article provides a critical review of why enterprise risk management (ERM) often fails to turn risk reports into timely risk actions. Drawing on behavioral finance (prospect theory) and bounded rationality, we explain how cognitive biases and attention constraints distort risk appraisal (probability/impact estimation and prioritization) and risk response (mitigation execution and escalation), creating a persistent gap in risk reporting and action. Agency theory and upper echelons theory clarify how incentive misalignment and executive biases shape organizational risk-taking, while institutional theory highlights ERM decoupling between formal structures and actual decision practices. We synthesize these perspectives into an integrative framework that positions ERM maturity and risk culture as mechanisms that can either transmit or buffer the effects of bias. Finally, the review then outlines a toolkit of bias-aware risk controls, standardized scenario framing, pre-mortems, independent challenge, action triggers, and stop-loss/kill criteria to strengthen strategic decision discipline.